2012
DOI: 10.1093/europace/eus060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of baseline P-wave duration and choice of atrial septal pacing site on shortening atrial activation time during pacing

Abstract: BackgroundAtrial septal pacing (ASP) has been shown to shorten P-wave duration (PWD) and reduce recurrence of atrial fibrillation (AF) in patients with bradyarrhythmias. However, variability of interatrial connections and atrial conduction properties may explain ASP's modest clinical benefit. The aim of this study was to assess the effect of ASP site on the duration of the paced P wave. Methods and resultsAtrial septal pacing at high atrial septum (HAS), posterior septum behind the fossa ovalis (PSFO), and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…• It was also demonstrated that, in patients with sinus node disease and intra-atrial conduction delay at the posterior triangle of Koch, low interatrial septum pacing was superior to right atrial appendage pacing in preventing progression to persistent or permanent atrial fibrillation 41 and is associated with the shortest atrial activation time compared with other atrial septal pacing sites in patients with prolonged P waves. 42 • On the other hand, the presence of increased P-wave duration has been described as an important parameter when programming the optimal AV delay in patients who require atrial pacing. In fact, it has been demonstrated that the adverse effect of interatrial delay in biventricular pacing may be avoided with interatrial septum pacing.…”
Section: Clinical Implications Of Interatrial Blocksmentioning
confidence: 99%
“…• It was also demonstrated that, in patients with sinus node disease and intra-atrial conduction delay at the posterior triangle of Koch, low interatrial septum pacing was superior to right atrial appendage pacing in preventing progression to persistent or permanent atrial fibrillation 41 and is associated with the shortest atrial activation time compared with other atrial septal pacing sites in patients with prolonged P waves. 42 • On the other hand, the presence of increased P-wave duration has been described as an important parameter when programming the optimal AV delay in patients who require atrial pacing. In fact, it has been demonstrated that the adverse effect of interatrial delay in biventricular pacing may be avoided with interatrial septum pacing.…”
Section: Clinical Implications Of Interatrial Blocksmentioning
confidence: 99%
“…Studies have observed that in patients with sinus node disease and intra-atrial conduction delay at the posterior angle of Koch, low interatrial pacing is superior compared to right atrial appendage pacing in preventing progression to persistent or permanent AF and is associated with the shortest atrial activation time compared with other atrial septal pacing sites in patients with IAB [32, 69, 70]. …”
Section: Common Myths and Under-known Facts About Iabmentioning
confidence: 99%